Implementing Sustainable Development Education in Research-Oriented Courses - Ummah Karimah Syarifuddin; Wiwied Widiyanti; Romlah Abdul Gany (STAI Hubbulwathan Duri, 2024)
Education for Sustainable Development (ESD) equips educators with the tools to integrate sustainability into teaching, focusing on themes such as disaster risk reduction, biodiversity, poverty alleviation, and sustainable consumption. This study investigates the implementation of ESD in research-based lectures, evaluating students' understanding, ability to develop research plans, and articulation of findings in academic articles. A descriptive survey approach was employed, using observational data collection during student research activities, documentation of research outputs, and student interviews. The study involved 85 Islamic Religious Education students at Muhammadiyah University Jakarta enrolled in a learning strategies course. Data were analyzed through triangulation of observations, interviews, and documented outputs. Students demonstrated competency in conducting ESD-focused research, as evidenced by their article preparation and group research outputs. Key indicators of success included the quality and depth of articles, meticulousness in material preparation, and active student involvement in group-based research activities. The integration of ESD into research-based learning fosters critical skills in sustainability research and academic communication. These findings suggest that structured, research-oriented pedagogical models enhance students' ability to engage with and contribute to sustainability goals. Research-based learning models in higher education effectively develop students' ESD competencies, including research planning and academic writing. The study highlights the potential of such models to prepare students as contributors to sustainability-oriented education and research.